Density functional theory study on the electronic properties of doped-cobalt oxide (CoO) - Siti Nurul Falaein Moridon,; Khuzaimah Arifin,; Amilia Linggawati,; Lorna Jeffery Minggu,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cobalt oxide (CoO) has been widely studied for photocatalyst of water splitting and displaying a high-efficiency material. This paper reports a Density Functional Theory (DFT) study on the electronic properties of rock-salt CoO and analyzes effects of cations (Ni and Fe) and anions (N and F) dopants on the electronic properties. For this purpose, CASTEP software used for first principles plane-wave pseudo-potential calculations at different functional, i.e: GGA-PW91 and LDA. The electronic calculations of the CoO optimized structure showed a metallic structure if without considering spin-orbital interactions. After considering the spin-orbital interaction calculation, the CoO band structure possessed indirect and direct band gaps. The direct bandgap by GGA-PW91 calculation is 2.10 eV, it was agreed to the experimentally reported value of approximately 1.9-2.6 eV. Meanwhile, Ni, Fe, and F-doped CoO, demonstrating decreased CoO direct band gaps to 1.70 eV, 1.80 eV, and 1.73 eV, respectively. While N-doped CoO increased the CoO direct bandgap to 3.05 eV. All dopants shifted the conduction and valence bands position, where Ni-doped CoO band edges keep straddle to the redox potential of water splitting. Among other elements in this study, Ni is a more desirable dopant of CoO to enhance photoelectrochemical hydrogen production.